Islands as eddy transformation and generation hotspots: Cabo Verde case study. (May 2020) - Cardoso, Cláudio; Caldeira, Rui M.A.; Relvas, Paulo; Stegner, Alexandre
Abstract: Deep-ocean islands have long been associated with the generation of oceanic eddies in their wakes. However, their interaction with incoming eddies has seldom been considered. This study focuses on the characterization of background and locally generated mesoscale eddies in the Cabo Verde archipelago between 2003 and 2014. Special attention is given to the interaction of incoming eddies with the bathymetry of the islands, along with their impacts on the local generation of eddies. Island-induced wind-shear effects are also considered. In addition, some examples of the biological response to background and locally generated eddies are discussed. This is achieved by combining remote-sensing satellite observations for wind, sea surface height, and chlorophyll- a (Chl a ) surface concentrations. The results show that the interaction between incoming background eddies and the archipelago is a recurrent phenomenon, which results in eddy deflection, splitting, merging, intensification, and termination (sorted by highest to lowest number of occurrences). Local island-induced disturbances are also significant, mainly due to atmospheric effects. Such processes result in the generation of island-induced eddies and in wind-mediated eddy intensification and confinement, more often observed in the leeward group. Nonetheless, it is strongly suggested that many of the locally generated eddies are a direct product or by-product of the interaction of background eddies with the islands. With respect to the biological realm, a locally generated cyclonic eddy is observed to originate a pronounced phytoplankton bloom in the vicinity of the tallest island. Nonetheless, background eddies generated off the African coast are often associated with enhanced Chl a concentrations when they intersect the archipelago. Such observations challenge the idea that local biological productivity in deep oceanic islands is exclusively driven by island-induced mechanisms.